2000
DOI: 10.1080/135457000750020155
|View full text |Cite
|
Sign up to set email alerts
|

India's New Economic Policy of 1991 and its Impact on Women's Poverty and AIDS

Abstract: This paper examines the effects of current policies intended to liberalize the Indian economy and facilitate globalization on women close to poverty. The New Economic Policy of 1991 included standard structural adjustment measures including the devaluation of the rupee, increase in interest rates, reduction in public investment and expenditure, reduction in public sector food and fertilizer subsidies, increase in imports and foreign investment in capital-intensive and high-tech activities, and abolition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…20–27). Second, in July 1991, India joined the globalization brigade by exposing its 1 billion people and a giant economy to neoliberal market forces and foreign direct investment that affected various groups (especially women) in many complex ways (Oza, 2001; Sadasivam, 1997; Upadhyay, 2000). Globalization facilitated a global exchange of ideas, a vibrant and mushrooming civil society, and global advocacy on HIV/AIDS prevention that connected global sex workers, global gays, and global queers with each other to share their concerns and build collective resistance against the dominant social order.…”
Section: The Indian Scene: Globalization Aids and The Discourse Of mentioning
confidence: 99%
“…20–27). Second, in July 1991, India joined the globalization brigade by exposing its 1 billion people and a giant economy to neoliberal market forces and foreign direct investment that affected various groups (especially women) in many complex ways (Oza, 2001; Sadasivam, 1997; Upadhyay, 2000). Globalization facilitated a global exchange of ideas, a vibrant and mushrooming civil society, and global advocacy on HIV/AIDS prevention that connected global sex workers, global gays, and global queers with each other to share their concerns and build collective resistance against the dominant social order.…”
Section: The Indian Scene: Globalization Aids and The Discourse Of mentioning
confidence: 99%
“…Sources: Schoepf (1988), Beneria and Feldman (1992), Grootaert (1994), Buchmann (1996), Upadhyay (2000), and Mohindra (2007). Notes: a While the available studies generally did not explicitly link the economic and education consequences of structural adjustment on the health of girls and women, we expanded on authors' suggested links based on the large body of evidence on the social determinants of women's health (cf.…”
Section: Case Study 1 -Women's Health and The Era Of Structural Adjusmentioning
confidence: 99%
“…Within rural settings, men are more likely to own land and technology or work in higher-paid roles in agriculture ( Agarwal, 1994 ); in urban communities, low female employment earnings and high dependency on male family members contributes to female poverty ( Banerjee, 1998 ). Additionally, the increasing industrialisation of urban areas has led to mass labour migration to these regions, whilst a lack of informal work for women has led them to take precarious work ( Upadhyay, 2000 ;Kapadia, 2010 ). Women's participation in the Indian economic sphere is increasing mainly through acceleration in the service sector (see Ghadially, 2007 ).…”
Section: Gender Equality and Development In Indiamentioning
confidence: 99%